Unusual Congenital Lesion Masquerading as a Lung Mass in an Adult - Singh, Vartika; Sudhesh, Kotian Shravya; Prasad HL, Kishan; Hosmane, Giridhar Belur; Gopalakrishnan, Mundayat; Shetty K, Jayaprakash (Journal of Health and Allied Sciences NU, 2021)
Congenital pulmonary airway malformation (CPAM) is a broad spectrum of congenital cystic lung lesions caused by the arrested bronchoalveolar development. Approximately, 80% of CPAMs are diagnosed prenatally or during the neonatal period when patients present with respiratory failure and cyanosis. CPAM is often associated with other organ anomalies and aplasia, and they have poor prognoses. Many CPAMs are detected in infants and school-age children, and infections like pneumonia trigger these diagnoses. It rarely manifests in adults. These often get missed because of the superadded diseases, and hence, it is essential to have a correct approach to their diagnosis to avoid misdiagnosis.
Keywords: congenital pulmonary airway malformation; cystic; bronchoalveolar